Eco-Friendly Antifungal from Seven Botanical Extracts and Its Effect To Plant Pathogenic Fungi - Simanjuntak, Juniarto Gautama; Ulfa, Aulia; Putri, Savira Rahma Apriliya; Aisyah; Puspitasari, Raditya Febri; Putra, Ivan Permana (Jurnal Sumberdaya Hayati, 2024)
Fusarium oxysporum has been the enemy in agriculture due to the wide range of infections in the whole crop and postharvest. Botanical extracts in traditional medicine systems were considered valuable sources for discovering new antifungals. Thus, exploration to get antifungals from eco-friendly botanical extracts as an alternative to synthetic fungicides needs to be expanded. Therefore, this study aims to test the antifungal potential of seven eco-friendly botanical aquadest extracts against F. oxysporum in vitro. The antifungal potential test was done on PDA media and the mycelial growth data was collected every two days for seven days. There were three antifungal phenomena were observed. The pandan leaf extract had a 4% fungal inhibition zone (phenomenon I). The extract of banana leaf, Hibiscus flower, papaya leaf, guava twig (phenomenon II), orange peels, and betel leaf (phenomenon III) had no values of fungal inhibition zone. Thus, pandan leaves extract revealed a fungal inhibition while other six botanical extracts had not enough antifungal potential in vitro.